Bill Clinton : An American Journey : Great Expectations - Hamilton, Nigel (London Century, 2003)
A biography of America's first baby-boomer president offers an examination of Bill Clinton's background and career, from his Arkansas upbringing and education at Oxford to his early political life.
Include Illustration, Note, Bibliography and Index
Keywords: Presidents -- Clinton, Bill, 1946- -- United States -- Arkansas -- Governors -- Interviews -- Politics and government